1985
DOI: 10.1017/s0021859600043124
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Rhizobium strains and lentil (Lens culinaris Linn.) genotypes under salt stress

Abstract: SummaryThree strains of Rhizobium able to fix nitrogen in symbiosis with lentils in saline soil were screened. Nodulation pattern, N2-fixation and grain yield were all influenced by Rhizobium strain and lentil genotype. Genotypes DL-443 and Pant L-406 were found to be more salt tolerant than others, and gave the highest grain yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Graham & Parker (1964) showed that NaCl concentrations as high as 340 mM and as low as 30 mM could be lethal to rhizobia. Other workers have reported that the tolerance limits of rhizobia vary from 0.09 to 340 m~ NaCl (Douka, Xenoulis & Paradellis, 1984;Rai, Nasar, Singh & Prasad, 1985). Tolerance of high levels of NaC1, for example 750 mM, was reported for R. melifoti (Kassem, Capellano & Gounot, 1985), and 850 m~ NaCl for R. legurninosururn (Rai.…”
Section: The Effect Of Salts On Rhizobia and Bradyrhizobiamentioning
confidence: 96%
“…Graham & Parker (1964) showed that NaCl concentrations as high as 340 mM and as low as 30 mM could be lethal to rhizobia. Other workers have reported that the tolerance limits of rhizobia vary from 0.09 to 340 m~ NaCl (Douka, Xenoulis & Paradellis, 1984;Rai, Nasar, Singh & Prasad, 1985). Tolerance of high levels of NaC1, for example 750 mM, was reported for R. melifoti (Kassem, Capellano & Gounot, 1985), and 850 m~ NaCl for R. legurninosururn (Rai.…”
Section: The Effect Of Salts On Rhizobia and Bradyrhizobiamentioning
confidence: 96%
“…Of the legumes, lentil is more salt sensitive when compared to faba bean and soybean (Katerji et al, 2001(Katerji et al, , 2003. Salt stress can adversely affect nodulation and N 2 fixation (Rai & Singh, 1999;Rai et al, 1985) presumably by restricting growth of the root hairs and the potential sites of infection by Rhizobium. Some germplasm with tolerance to salt stress has been identified (Ashraf & Waheed, 1993;Ashraf et al, 1990;Jana & Slinkard, 1979).…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…Variation in tolerance to MgSO 4 , NaCl, Na 2 SO 4 and MgCl 2 was identified in the USDA World Lentil Collection (Jana and Slinkard 1979) but the level of tolerance was considered insufficient for breeding to continue (Muehlbauer and Slinkard 1983). The NaCl tolerant accessions DL443 and Pant L406 (Rai et al 1985), ILL5845, ILL6451, ILL6788, ILL6793 and ILL6796 (Ashraf and Waheed 1990) and LG128 (ILL3534) (Maher et al 2003) have been identified. A positive correlation was observed between degrees of salt tolerance at different stages of growth in the glasshouse (Ashraf and Waheed 1993a) and tolerance was based on the typical halophytic mechanism of salt inclusion Waheed 1993, Shah andMuhammad 1976).…”
Section: Salinitymentioning
confidence: 99%